Effect of Spinning Rate on Structure and Morphology of ZnO:Cu Thin Films Prepared using a Sol-gel Spin Coating Method - Hamid, Nur; Astuti, Budi; Dharma Putra, Ngurah Made; Marwoto, Putut; Sugianto, Sugianto; Muttaqin, Rodhotul; Setyaningsih, Natalia Erna (Universitas Negeri Semarang, 2020)
Cu-doped ZnO (ZnO:Cu) thin film was deposited on glass substrate using a sol-gel spin coating method. The film was prepared at various spinning rate followed by sintering at 250 Â°C for 10 min and annealing at 350 Â°C for 2 hours. The effect of spinning rate on structural properties was investigated by means of X-ray diffractometer (XRD), scanning electron microscope (SEM) equipped with energy dispersive X-ray (EDX). The diffraction pattern indicated that Cu-ZnO thin films showed a strong c-axis orientation, i.e. the peak attributed to (002) plane at a of corresponding to hexagonal wurtzite crystals. An increase in the spinning rate resulted in ZnO:Cu thin films with high homogeneity. It was further proved by SEM and EDX results.